PENINGKATAN KEAKTIFAN BELAJAR PESERTA DIDIK MATERI EKOLOGI MELALUI PENERAPAN MODEL PBL DI SMP - Ningsih, Yunia; Sati, Sati; Andayan, Iwan (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2025)
This research was motivated by the lack of student engagement in science learning. Science is often perceived as a difficult and abstract subject, leading to low enthusiasm and passive participation among students during the learning process. The purpose of this study is to enhance student learning engagement through the implementation of the Problem-Based Learning (PBL) model combined with a differentiated instruction approach in the ecology topic at SMP Negeri 2 Weru.The research method employed is classroom action research, which was conducted over two instructional cycles. Each cycle consisted of four stages: planning, implementation, observation, and reflection.The research findings indicate that prior to the intervention, the percentage of active student participation was only 49.38%, categorized as low. After the first cycle, student engagement increased to 68.06%, falling into the moderate category. In the second cycle, a significant improvement was observed, with student engagement reaching 85.96%, categorized as high. The results of the study conclude that there was a notable increase in student learning engagement following the application of the PBL model integrated with a differentiated instruction approach. ABSTRAKKurangnya partisipasi belajar peserta didik dalam Pembelajaran IPA. Peserta didik cenderung kurang aktif, tidak terlibat, bahkan tidak berminat dalam mempelajari IPA karena dianggap rumit dan konseptual. Tujuan penelitian ini adalah untuk meningkatkan partisipasi belajar peserta didik melalui penerapan model Problem Based Learning (PBL) dengan pendekatan diferensiasi pada materi ekologi di SMP Negeri 2 Weru. Metode penelitian yang digunakan adalah penelitian tindakan kelas, yang dilakukan dalam dua siklus pembelajaran. Setiap siklus terdiri dari empat tahap, yaitu perencanaan, pelaksanaan, pengamatan, dan refleksi. Berdasarkan hasil penelitian, menunjukkan bahwa sebelum tindakan diambil, persentase aktivitas belajar peserta didik hanya mencapai 49,38% dalam kategori rendah. Setelah pelaksanaan Tindakan pada siklus I, tingkat keaktifan mencapai 68,06% dalam kategori sedang. Pada siklus II, tingkat keberhasilan keaktifan belajar peserta didik mengalami peningkatan yang signifikan, mencapai 85,96% dalam kategori tinggi. Temuan penelitian menunjukkan bahwa penerapan model pembelajaran PBL yang dikombinasikan dengan pendekatan diferensiasi meningkatkan keaktifan belajar peserta didik.